Influenza A(H1N1)pdm09 virus and asthma - Obuchi, Masatsugu; Adachi, Yuichi; Takizawa, Takenori; Sata, Tetsutaro (Frontiers in Microbiology, 2013)
Respiratory viral infection is a major cause of asthma exacerbations in both children and adults. Among the respiratory viruses, influenza virus is a particularly important pathogen due to its enormous morbidity and mortality in annual epidemics. The swine-origin influenza A virus, designated as A(H1N1)pdm09, emerged in the spring of 2009 and caused the first influenza pandemic in the 21st century. With the emergence of the novel A(H1N1)pdm09 virus, numerous epidemiologic studies detected asthma as a frequent comorbid condition in patients infected with this virus. Here we review recent reports regarding asthma in patients infected with influenza A(H1N1)pdm09 virus, and we discuss the utility of influenza vaccines and antivirals.